Pelvic Surgical Site Infections in Gynecologic Surgery - Mark P. Lachiewicz; Laura J. Moulton; Oluwatosin Jaiyeoba (Hindawi Limited, 2015)
The development of surgical site infection (SSI) remains the most common complication of gynecologic surgical procedures and results in significant patient morbidity. Gynecologic procedures pose a unique challenge in that potential pathogenic microorganisms from the skin or vagina and endocervix may migrate to operative sites and can result in vaginal cuff cellulitis, pelvic cellulitis, and pelvic abscesses. Multiple host and surgical risk factors have been identified as risks that increase infectious sequelae after pelvic surgery. This paper will review these risk factors as many are modifiable and care should be taken to address such factors in order to decrease the chance of infection. We will also review the definitions, microbiology, pathogenesis, diagnosis, and management of pelvic SSIs after gynecologic surgery.